Mode of Transmission, Rather than the Hepatitis C Virus, as a Major Determinant of Poor Interpersonal Relationships in Patients with Chronic Hepatitis C. (2007) - La, Thuy Phuong; Deschênes, Marc
Abstract : BACKGROUND: Recent studies have demonstrated that patients with the hepatitis C virus (HCV) have significant neurocognitive impairment. OBJECTIVE: To assess whether chronic HCV infection impacts on patient marital status, living arrangement and employment. METHODS: The charts of patients with chronic hepatitis C and hepatitis B were reviewed. RESULTS: The mean (± SD) age of the 129 patients with the hepatitis B virus (HBV) was 46±15 years and that of the 428 patients with HCV was 48±15 years. Sixty-seven per cent of HBV patients were men, compared with 68% of HCV patients. Eighty per cent of HCV patients were Caucasian, compared with 44% of patients with HBV. The main modes of transmission were intravenous drug use (37%) and transfusion of blood products (37%) for HCV, compared with country of origin (76%) for HBV. There were no differences in marital status rates between HBV- and HCV-infected patients (HBV – married (73%), single (21%) and divorced (6%); and HCV – married (66%), single (23%) and divorced (10%); P=0.20). HCV patients lived alone more often than HBV patients (HBV – 13%, HCV – 22%; P=0.03). There was no difference in overall employment rate between HCV and HBV patients (81% versus 87%; P=0.15). Though there may not have been overall differences between HCV and HBV marital status and employment status, there were differences in the HCV subgroups. These subgroup differences were discovered in the multivariate analysis; mode of transmission was identified as the only predictor of the patients' marital status and employment status. CONCLUSIONS: The most important determinant of interpersonal relationships was the mode of transmission of the viral hepatitis rather than the type of viral infection: past intravenous drug users had lower level relationships.